Analysis of immune response induction mechanisms implicating the dose-sparing effect of transcutaneous immunization using a self-dissolving microneedle patch. Issue 6 (7th February 2022) - Ito, Sayami; Hirobe, Sachiko; Yamashita, Ryo; Sugiyama, Arisa; Takeuchi, Honoka; Eguchi, Ryosuke; Yoshida, Junya; Oyamada, Takayoshi; Tachibana, Masashi; Okada, Naoki
Abstract: Transcutaneous immunization (TCI) is an effective vaccination method that is easier and less painful than the conventional injectable vaccination method. We previously developed self-dissolving microneedle patches (sdMN) and demonstrated that this TCI method has a high vaccination efficacy in mice and humans. To elucidate the mechanism of immune response induction, which is the basis for the efficacy and safety of TCI with sdMN, we examined the local reaction of the skin where sdMN was applied and the kinetics and differentiation status of immune cells in the draining lymph nodes (DLNs). We found that gene expression of the proinflammatory cytokine Il1b and the downstream transcription factor Irf7 was markedly upregulated in skin tissues after sdMN application. Moreover, activation of Langerhans cells and CD207 − dermal dendritic cells, which are subsets of antigen-presenting cells (APCs) in the skin, and their migration to the DLNs were promoted. Furthermore, the activated APC subsets promoted CD4 + T cell and B cell differentiation and the formation of germinal centers, which are the sites of high-affinity antibody production. These phenomena associated with sdMN application may contribute to the efficient production of antigen-specific antibodies after TCI using sdMN. These findings provide essential information regarding immune response induction mechanisms for the development and improvement of TCI preparations.